A serendipitous case report of acute pancreatitis complicated by pseudocyst in a patient with COVID-19 - Shenoy, Vallish; Baindur, Aditya J. J (International Surgery Journal, 2021)
Acute pancreatitis is a common gastrointestinal disease, most frequently requiring acute hospitalization. During SARS-CoV-2 (severe acute respiratory syndrome coronavirus-2) pandemic, the etiologic agent of COVID-19, several studies described the involvement of other tissues besides the respiratory tract, such as the gastrointestinal tract. In pancreas, ACE-2 receptor is expressed in exocrine glands and islets, both being targets for the virus and subsequent pancreatic injury. There are few articles which report pancreatic injury in COVID-19 patients but most of them do not report acute pancreatitis. Diagnosing acute pancreatitis in the setting of COVID-19 pandemic is challenging and requires ruling out all other potential causes of pancreatitis. Herein we report a rare case of severe acute pancreatitis.